Adductor Strains in Athletes - Malachy P McHugh; Stephen J Nicholas; Timothy F Tyler (International Journal of Sports Physical Therapy)
Acute adductor injuries are a common occurrence in sport. The overall incidence of adductor strains across 25 college sports was 1.29 injuries per 1000 exposures, with men's soccer (3.15) and men's hockey (2.47) having the highest incidences. As with most muscle strains there is a high rate of recurrence for adductor strains; 18% in professional soccer and 24% in professional hockey. Effective treatment, with successful return to play, and avoidance of reinjury, can be achieved with a proper understanding of the anatomy, a thorough clinical exam yielding an accurate diagnosis, and an evidence-based treatment approach, including return to play progression.